A review of hydrologic signatures and their applications - McMillan, Hilary K. (Wiley interdisciplinary reviews. Water, 2021)
Hydrologic signatures are quantitative metrics or indices that describe statistical or dynamical properties of hydrologic data series, primarily streamflow. Hydrologic signatures were first used in eco‐hydrology to assess alterations in flow regime, and have since seen wide uptake across a variety of hydrological fields. Their applications include extracting biologically relevant attributes of streamflow data, monitoring hydrologic change, analyzing runoff generation processes, defining similarity between watersheds, and calibrating and evaluating hydrologic models. Hydrologic signatures allow us to extract meaningful information about watershed processes from streamflow series, and are therefore seeing increasing use in emerging information‐rich areas such as global‐scale hydrologic modeling, machine learning, and large‐sample hydrology. This overview paper describes the background and development of hydrologic signature theory, reviews hydrologic signature use across a variety of applications, and discusses ongoing hydrologic signature research including current challenges. This article is categorized under: Science of Water > Science of Water Hydrologic signatures are metrics that we use to describe the complex dynamics of river flow.